ANALISIS JALUR FAKTOR SOSIAL EKONOMI TERHADAP KESEJAHTERAAN MASYARAKAT DI TIMIKA PAPUA TENGAH - Sara Tamariska Massolo; Nova Linda (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze the direct and indirect effects of socio-economic factors on community welfare in Timika using a path analysis approach. The independent variables in this study include education level and income, while employment opportunities act as a mediating variable, and community welfare is the dependent variable. A quantitative research method was employed, with data collected through surveys of residents in the Timika area. Path analysis was used to identify the causal relationships among variables simultaneously. The results indicate that education level and income have a significant effect on employment opportunities, which in turn influence community welfare. Additionally, indirect effects were found to strengthen the relationship between the independent variables and welfare. This study is expected to serve as a reference for local governments in formulating development policies focused on improving the quality of human resources in Timika